Nanostructures for Photonics and Optoelectronics - Vicente Torres-Costa (Nanomaterials, 2022)
As microelectronic technology approaches the limit of what can be achieved in terms of speed and integration level, there is an increasing interest in moving from electronics to photonics, where photons and light beams replace electrons and electrical currents, which will result in higher processing speeds and lower power consumption [...]